2020
DOI: 10.1002/hbm.25254
|View full text |Cite
|
Sign up to set email alerts
|

Functional neuroanatomy of language without speech: An ALE meta‐analysis of sign language

Abstract: Sign language (SL) conveys linguistic information using gestures instead of sounds. Here, we apply a meta‐analytic estimation approach to neuroimaging studies (N = 23; subjects = 316) and ask whether SL comprehension in deaf signers relies on the same primarily left‐hemispheric cortical network implicated in spoken and written language (SWL) comprehension in hearing speakers. We show that: (a) SL recruits bilateral fronto‐temporo‐occipital regions with strong left‐lateralization in the posterior inferior front… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
41
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
4
3
3

Relationship

4
6

Authors

Journals

citations
Cited by 55 publications
(76 citation statements)
references
References 94 publications
(169 reference statements)
10
41
0
Order By: Relevance
“…Our findings are in line with recent models implicating these posterior portions of temporal lobe in phrase structure building (Flick and Pylkkänen, 2020; Matchin and Hickok, 2020; Murphy, 2018, 2020), a recent meta-analysis of sign language implicating TOJ and pMTG/pSTS in comprehension (Trettenbrein et al, 2020), and the finding that cross-linguistic (French and Chinese) reading competence is linked to pSTS (Feng et al, 2020), contributing to the neural localization of a modality-independent compositional operator (Chomsky et al, 2019; Pietroski, 2018), an essential component of language. In particular, evidence from neuroimaging and lesion-deficit mapping indicates a role for pMTG in syntactic comprehension and production (Matchin and Hickok, 2020), while pSTS has been implicated via iEEG in hierarchical syntactic computations (Nelson et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings are in line with recent models implicating these posterior portions of temporal lobe in phrase structure building (Flick and Pylkkänen, 2020; Matchin and Hickok, 2020; Murphy, 2018, 2020), a recent meta-analysis of sign language implicating TOJ and pMTG/pSTS in comprehension (Trettenbrein et al, 2020), and the finding that cross-linguistic (French and Chinese) reading competence is linked to pSTS (Feng et al, 2020), contributing to the neural localization of a modality-independent compositional operator (Chomsky et al, 2019; Pietroski, 2018), an essential component of language. In particular, evidence from neuroimaging and lesion-deficit mapping indicates a role for pMTG in syntactic comprehension and production (Matchin and Hickok, 2020), while pSTS has been implicated via iEEG in hierarchical syntactic computations (Nelson et al, 2017).…”
Section: Discussionsupporting
confidence: 92%
“…This proposal is strengthened if one looks at the case of sign language (Trettenbrein et al 2021). This is obviously also a cultural invention, and does not involve phonemes as it is a communication means for deaf people.…”
Section: Naturalness and Evolution Of Reading And Writingmentioning
confidence: 99%
“…This theoretical interest has been accompanied by an upsurge of psycholinguistic and neurolinguistic studies on sign language processing in different labs around the world, thus contributing to a deeper level of understanding of the human capacity for language. These studies have revealed important similarities and differences between modalities with regard to both psychological processes (Gutiérrez, Müller, Baus, & Carreiras, 2012;Gutiérrez, Williams, Grosvald, & Corina, 2012;Hosemann, Herrmann, Sennhenn-Reulen, Schlesewsky, & Steinbach, 2018;Vinson, Thompson, Skinner, Fox, & Vigliocco, 2010) and the underlying neural representation (Emmorey, 2015;MacSweeney, Capek, Campbell, & Woll, 2008;Trettenbrein, Papitto, Friederici, & Zaccarella, 2021). Reaction time studies, eye tracking experiments, and electroencephalography investigations of spoken and written and, more recently, sign language processing have underlined the importance of controlling for lexical variables such as frequency and age of acquisition (AoA) in psycholinguistic experiments.…”
Section: Introductionmentioning
confidence: 99%